Effect Of Pre Marital Education On Attitudes Towards Preventing High-Risk Pregnancies In Prospective Brides And Grooms At Sooko Health Center Mojokerto Regency - Siti Fatimah; Retno Palupi Yonni Siwi (Journal of Health Science Community, 2025)
High risk pregnancy was a pregnancy that causes greater risks and complications for the mother and fetus in the womb, and can result in death, morbidity, disability, discomfort and dissatisfaction. The aim of this research was to determine the effect of pre-marital education on attitudes towards preventing high-risk pregnancies in prospective brides and grooms. This research design was pre-experimental with a one group pretest-posttest design approach. The independent variable was premarital education and the dependent variable was attitude towards preventing high risk pregnancies. The population was all prospective brides and grooms at the Sooko Community Health Center, Mojokerto Regency, a sample of 32 respondents using accidental sampling technique. The data collection technique uses a questionnaire.The research results showed that before being given treatment, the majority of respondents (65.6%) had a negative attitude and after being given treatment, almost all respondents (75.0%) had a positive attitude in preventing high-risk pregnancies. The results of data analysis using the Wilcoxon test to analyze obtained a sig (2-tailed) value or pvalue = 0.002 and an error level of or = 0.05, so p <, 0.002 < 0.05 so that H1 was accepted, meaning there was an influence of premarital education on attitudes prevention of high risk pregnancies in prospective brides and grooms at the Sooko Community Health Center, Mojokerto Regency.The use of media in providing health education greatly influences a person's attitudes and intentions in avoiding high-risk pregnancies.Receiving good information will have an impact on understanding what is seen and heard so that it can change a person's attitude from negative to positive.